The role of negotiation for long-haul markets in the intention of revisit rural - Rodrigues, A.; Marques, C. (Proceedings of the 5th Advances in Tourism Marketing Conference (ATMC 2013), 2013)
In the last decades a growing demand for alternative forms of tourism is observable, with rural areas becoming more and more searched and chosen as tourist destinations, mainly for the contact with traditional ways of life, traditions and outdoor recreational opportunities by the so called postmodern tourists. Most of the rural tourists are from within European countries, and there is a lack of long-haul tourists in those rural destinations. According to several authors, the relevance of understanding the pattern of visiting several destinations during one holiday trip is more evident for tourists that have to overcome longer distances (Teye, 1989). However, this reality has not attracted much attention amongst researchers and several authors underline the need to understand this type of travel behaviour more profoundly. Particularly in the European context, the travel behaviour of long-haul travellers has been recognized as very important. One of the major long-haul markets for Europe is the North-American market which generally does not repeat visitation for Europe, especially for rural places, and consequently becoming non-visitors. Being a long-haul market there could be a maximization of the tourism offer of Europe between urban and rural destinations. In a previous study undertaken in the Mid-Atlantic US it was verified that this market faces several constraints to travel to Europe (Rodrigues, 2012). This behaviour chance may be due to some constraints to travel that may be struggling to visit the destination. Therefore, it is important to know what are the main constraints to travel and also the negotiation factors that could transform a non-visitor into a repeat or frequent visitor. In this study we discuss the intention of North-Americans to return and revisit rural places in Europe. In particular it is studied the influence of the travel constraints and the negotiation factors on the intentions to revisit European rural destinations for the North-Americans long-haul market.